2002
DOI: 10.1021/jf020316l
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of Natural Vanilla Flavorings:  Isotopic Characterization Using Degradation of Vanillin into Guaiacol

Abstract: The isotopic investigation of vanillin has been extended to the new sources of natural precursors of vanillin recently introduced with a view of obtaining natural vanillin by biotechnological processes. To check the consistency of the isotopic composition of vanillin with that of the corresponding aromatic fragment, a selective degradation reaction into guaiacol was carried out. The reaction was shown to proceed without significant isotopic fractionation at the sites of interest, and an optimized procedure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 12 publications
(25 reference statements)
7
60
0
Order By: Relevance
“…Moreover, vanillin displays antimicrobial and antioxidant properties and is used as a food preservative and for medicinal purposes (10 -15). Natural vanilla flavor from the orchid Vanilla planifolia (16,17) supplies Ͻ1% of the total demand for vanillin. Therefore, because of the increasing interest in natural products, alternative processes are being developed to produce natural vanillin (15, 18 -20).…”
mentioning
confidence: 99%
“…Moreover, vanillin displays antimicrobial and antioxidant properties and is used as a food preservative and for medicinal purposes (10 -15). Natural vanilla flavor from the orchid Vanilla planifolia (16,17) supplies Ͻ1% of the total demand for vanillin. Therefore, because of the increasing interest in natural products, alternative processes are being developed to produce natural vanillin (15, 18 -20).…”
mentioning
confidence: 99%
“…Of the chocolate bars and chocolate snack foods in Table 1, the samples 1, 3,7,8,9,10,11, and 12 were declared as "vanilla" on the label. Only samples 3 and 11 gave results that agreed with this declaration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…7 Site-specific natural isotope fractionation combined with nuclear magnetic resonance (SNIF−NMR) measurements has produced data that define the site-specific abundance of deuterium or carbon-13. 8,9 Several reports have shown that 2 H NMR spectroscopy allows for the determination of the synthetic or natural origin of vanillin as well as providing information about the starting materials. 6,8−12 The determination of stable isotope ratio mass spectrometry of carbon is presently a useful method for discrimination between natural vanillin from vanilla beans and synthetic vanillin or that produced from biotechnological methods.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The replacement of VAN with EVA inevitably results in the use of the flavoring in artificial products because the presence of this compound is a unambiguous evidence of their non-natural origin. However, the presence of VAN in vanilla-related samples is not unequivocal proof of their authenticity because adulteration of vanilla extracts with synthetic VAN (lignin-derived) is a major problem in commercial products [18][19][20][21]. As a consequence, the high demands and the high price of authentic vanilla extracts leads to numerous attempts to blend and adulterate samples and their authenticity must be verified by MS or by multianalyte detection in vanilla extract profiles using GC and HPLC [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%